Composição florística e fatores associados ao solo que determinam traços funcionais da vegetação lenhosa em duas fitofisionomias da caatinga: carrasco versus mata seca - Marques, Antonia Mirelle Lopes (2024)
The Caatinga, a biome of approximately 850,000 km2, is characterized by low rainfall and high temperatures, and is home to a remarkable diversity of Seasonally Dry Tropical Forests (SDTF), such as Carrasco and Sedimentary Dry Forest. Distinct phytophysiognomies arise due to the vastness and diverse factors, such as soil, resulting in preservation challenges due to inadequate exploitation, human activities and climate change. The study at the Patrimônio Natural Serra das Almas (RNSA) aimed to understand Carrasco and Mata Seca by analyzing their floristic composition and functional traits. It used the Field Manual for Plot Establishment and Remediation - DryFlor, Rainfor's soil and leaf content analysis protocols, and the Manual for Standardized Measurement of Plant Functional Traits developed by Perez-Harguindeguy. Phytosociological analysis using Fitopac 2.1, PCA and LDA highlighted differences in the soil's physical and chemical properties, indicating an influence on species selection. Carrasco had sandy loam soil with Quartzarenic Neosol, while Mata Seca had sandy loam soil, Litholic Neosol, with less depth. In terms of flora, Carrasco was home to 708 individuals, 13 families, 24 genera and 31 species, with Fabaceae, Myrtaceae, Euphorbiaceae and Apocynaceae standing out. The Dry Forest had 1057 individuals, 19 families, 32 genera and 41 species, with Fabaceae, Myrtaceae, Apocynaceae, Euphorbiaceae, Combretaceae, Celastraceae and Rubiaceae being the most representative. Carrasco had a Shannon index of 2.124 nats/ind-1 and a Pielou equability of 0.61. In the Dry Forest, a Shannon index of 2.988 nats/ind-1 was recorded, accompanied by a Pielou equability of 0.79. PCA revealed no significant differences in functional traits, but LDA identified average height, nitrogen (N) and carbon (C) concentrations as discriminating between Carrasco and Mata Seca. Both areas face similar climatic filters, with soil being the main environmental factor. Although Mata Seca has a higher water content, both receive the same annual rainfall. The study observed a higher concentration of leaf carbon in Mata Seca, in line with global patterns associated with precipitation and temperature. However, the limitations of the traits analyzed indicate the need for further research into stem and leaf anatomy for a more detailed and clear understanding of the distinct phytophysiognomies of Carrasco and Mata Seca.